The APPLICATION OF SWEDISH MASSAGE TO RISK PERIPHERAL PERFUSION IN EFFECTIVE PATIENT HYPERTENSION IN THE WORK AREA SIMPANG PERIUK PUBLIC HEALTH CENTER LUBUK LINGGAU CITY YEAR 2022 - Nadi Aprilyadi; Yeni Elviani; Maya Wardani (Lembaga Pengembangan Kinerja Dosen, 2022)
ABSTRACK Background: According to the World Health Organization (WHO), hypertension is a condition where the increase in systolic blood is above the normal limit, which is more than 140 mmHg and diastolic blood pressure is more than 90 mmHg. Hypertension can increase the workload of the heart and arteries which if it continues can cause damage to the heart and blood vessels. Swedish massage therapy is a complementary therapy that is believed to be able to provide a relaxation response, beside that it can also reduce blood pressure. Research Purpose: The purpose of this research was to obtain an overview of nursing care in the implementation of Swedish Massage to elderly hypertension sufferers at the Simpang Periuk Public Health Center, Lubuklinggau City. The Research Method: The research method was descriptive with a case study approach. The subjects of this study were two elderly people in the work area of Simpang Periuk Public Health Center, Lubuklinggau City. The Evaluation Results: The evaluation results that was obtained from the management of a decrease in blood pressure after the Swedish Massage intervention was done to the hypertensive patients with both elderly subjects with the changes in blood pressure of 10 mmHg. The conclusion: The conclusion from the research was that the implementation of Swedish Massage is an intervention that can be done to reduce the symptoms that arise due to high blood pressure. This technique is one of the non-pharmacological techniques that can be used to minimize high blood pressure. Suggestions: Suggestions were expected to increase knowledge and can be done independently to lower blood pressure.Keywords: Hypertension, Blood Pressure, Swedish Massage